Distribution of Zonula Occludens-1 and Occludin and alterations of testicular morphology after in utero radiation and postnatal hyperthermia in rats - ERCAN, FERİHA (WILEY, 2012)
In utero irradiation (IR) and postnatal hyperthermia (HT) exposure cause infertility by decreasing spermatogenic colony growth and the number of sperm in rats. Four groups were used: (i) Control group, (ii) HT group (rats exposed to hyperthermia on the 10th postnatal day), (iii) IR group (rats exposed to IR on the 17th gestational day) and (iv) IR + HT group. Three and six months after the procedures testes were examined by light and electron microscopy. Some degenerated tubules in the HT group, many vacuoles in spermatogenic cells and degenerated tight junctions in the IR group, atrophic tubules and severe degeneration of tight junctions in the IR + HT group were observed. ZO-1 and occludin immunoreactivity were decreased and disorganized in the HT and IR groups and absent in the IR + HT group. The increase in the number of apoptotic cells was accompanied by a time-dependent decrease in haploid, diploid and tetraploid cells in all groups. Degenerative findings were severe after 6 months in all groups. The double-hit model may represent a Sertoli cell only model of infertility due to a decrease in spermatogenic cell and alterated blood-testis barrier proteins in rat.
Keywords: apoptosis; blood-testis barrier; hyperthermia; irradiation; rat; testis; SEMINIFEROUS TUBULES; SINGLE EXPOSURE; CELL-DEATH; TESTIS; SERTOLI; SPERMATOGENESIS; APOPTOSIS; IRRADIATION; EXPRESSION; HEAT